Body image and its association with depression, anxiety, and self-esteem among college going students: A study from Northeast India - Ibanlumlin Diengdoh; Arif Ali (Wolters Kluwer Medknow Publications, 2022)
Background: Body image is conceptualized as a subjective perception of an individual one's own body and on how he/she is seen by others, and its distortion can lead to poor self-esteem and affect psychological adjustment among the youth. The objectives of the study were to assess body image and to see the association with depression, anxiety, and self-esteem among students. Materials and Methods: A cross-sectional correlational study was conducted among undergraduate students in Shillong, Meghalaya. The researcher used random sampling as for the selection of college. The Krejcie and Morgan (1970) sampling method was used to determine the sample size by a table using the sample size formula for the finite population. A total of 384 respondents were selected for the study, out of which 358 were included for the final analysis. Sociodemographic datasheet, Multidimensional Body-Self Relations Questionnaire-Appearance Scales, Rosenberg Self-Esteem Scale, Beck Depression Inventory-II, and Hamilton Anxiety Rating Scale were administered. Results: Regression analysis showed self-esteem and anxiety contribute significantly to the prediction of body image satisfaction among students (F[4353] = 3.816, P = 0.001), accounting for a 15.1% variance. Conclusion: Significant proportion of students were dissatisfied with their body image. Furthermore, a study reported that body image influences psychological well-being. There is a need for preventive measures and making these young people aware of the importance of both physical and mental health.